Pengembangan Media Diorama pada Pembelajaran Tematik Tema Ekosistem di Kelas V SD Putra Bangsa Berbudi - Batubara, Widia Putriana; Juwita, Putri (JURNAL PENELITIAN PENDIDIKAN MIPA, 2025)
This research aims to develop diorama media with an ecosystem theme that is suitable for use in thematic learning on the theme "Ecosystem" in class V elementary school. This research is development research (Research and Development) using the ADDIE development procedure which consists of 5 stages. The test subjects in this research were media experts, material experts, learning experts and student responses. The object in this research is ecosystem theme diorama media which is suitable for use in the learning process in class V. The instrument used to collect data is a validation questionnaire given to several expert validators, namely media expert validators, material expert validators and learning expert validators. The total score obtained from validation by media experts was 94.6, from validation by material experts, namely 86, from learning experts it was 93 and from student responses a score was obtained of 97. The average score from the experts' assessments was 92.65. From this score it can be said that the ecosystem theme diorama media developed is "Very Suitable" for use in the thematic learning process in class V of Putra Bangsa Berbudi Elementary School, Deli Tua.